Improving Fucoxanthin Production in Mixotrophic Culture of Marine Diatom Phaeodactylum tricornutum by LED Light Shift and Nitrogen Supplementation - Yang, Runqing; Wei, Dong (Frontiers in Bioengineering and Biotechnology, 2020)
Fucoxanthin (Fx), a kind of primary carotenoids in brown seaweeds and diatoms, has attractive efficacy in human’s healthcare including loss weight, the prevention of diabetes and Alzheimer’s disease. Marine diatom Phaeodactylum tricornutum is now realized as a promising producer for commercial Fx production due to its higher content of Fx than brown seaweeds with easily artificial cultivation and Fx extraction. In the present study, to improve Fx production in P. tricornutum, the mixotrophic cultures were applied to optimize initial cell density, light intensity, light regime and nitrogen supplementation. The results showed that the higher initial cell density (1 × 107 cells mL–1) and lower light intensity (20 μmol m–2 s–1) were favorable for biomass production and Fx accumulation. The maximal Fx content [16.28 mg g–1 dry weight (DW)] could be achieved under blue light (BL), but the highest biomass concentration (5.53 g L–1) could be attained under red: blue light (R: B, 6:1) in the batch culture. A novel two-phase culture approach was developed to increase the biomass concentration to the highest value (6.52 g L–1) with the maximal productivity of Fx (8.22 mg L–1 d–1) through light shift from R:B ratio (6:1) in phase 1 to R:B ratio (5:1) by enhancing BL and tryptone addition in phase 2. The content and intracellular amount of Fx were also increased 8% and 12% in phase 2 compared to phase 1. The expression levels analysis revealed that genes encoding phytoene synthase (PSY), zeaxanthin epoxidase (ZEP), and fucoxanthin-chlorophyll-protein b (FCPb) were upregulated significantly, with downregulation of the gene encoding violaxanthin de-epoxidase (VDE), leading to the improvement of Fx in phase 2. The present study demonstrated the two-phase culture strategy could promote Fx productivity through enhancing biomass production and increasing Fx content, indicating that strengthening BL coupled with adding tryptone were effective to facilitate Fx production by mixotrophic cultivation of marine diatom P. tricornutum.